On Byzantine Reaction to the Council of Pisa in 1409 - Nikolai Gennadjevich Pashkin (Античная древность и средние века, 2019)
The Council of Pisa in 1409 made an attempt to complete the history of the Great Western Schism. The result was election of the Pope Alexander V (1409–1410). In few months Byzantine Emperor Manuel II Palaeologos sent him the letter of greeting. He expressed his gladness in connection with the restored unity of Western Church and promised in the future to send a diplomat. However, the Council of Pisa did not stop the Schism indeed. Not all the Latin states recognized the new Pope, and previous two antipopes Gregory XII and Benedict XIII were not going to abdicate. Besides Byzantine Emperor said nothing of the goal of probable negotiations with Alexander V. So we have to look for a particular diplomatic sense in the letter of greeting to the Pope. It can be found in the history of international relations, that influenced upon the preparation for and the organization of the Council of Pisa. Florence and France were evident supporters of the Council. Their opponent was Neapolitan King Ladislaus, who at the same time was the titular King of Hungary. Germany divided into supporters of German King Rupert and Czech King Wenceslaus. The result was the alliance of Wenceslaus and the new Pope. At first common neutral stance united Venice and Hungarian King Sigmund of Luxembourg. They maintained relations with the Pope Gregory XII, but admitted his voluntary abdication for stopping of the Schism. However, the analysis of results of the Council shows that it reproduced the advantageous generally for Venice alignment of international forces. In few weeks after election of Alexander V the Republic suddenly shifted its ground and recognize him. But at first it bought from the King Ladislaus titulary rights to Dalmatia, that was considered the possession of the Hungarian Crown. This was leading to the complication in its relations with the King Sigmund. Their conflict in the Balkans provoked the feud in the Ottoman state, that threatened the Byzantine Empire. Only the mediation of the Pope Alexander V could avert the conflict, but Sigmund also had to recognize him. The letter of Byzantine Emperor purposed to contribute to this and join the Pope in the mediation between Hungary and Venice.